Rinoplastia estrutural com cartilagem costal em pacientes de hanseníase - Naves, Marcell de Melo (2013)
Introduction: Social reintegration is one of the most challenge for those affected by saddle nose deformity due to leprosy. The nasal reconstruction becomes extremely important in the rehabilitation of disfigured victims. This study aimed to describe the technique of structural rhinoplasty with autologous costal cartilage for nasal reconstruction in patients with saddle nose deformity due to leprosy and evaluate the aesthetic results, functional and patient. Methods: A descriptive study was conducted evaluating 10 patients with lepromatous leprosy, who had saddle nose, followed at the National Reference Center for Sanitary Dermatology and Leprosy (CREDESH) / HC / UFU, who underwent structural rhinoplasty with costal cartilage graft, which had already been discharged from polychemotherapy and there were at least one year without leprosy reaction. Results: The preoperative symptoms were, more common, aesthetic complaints and nasal obstruction (100%), followed by nasal crusting (80%), epistaxis (70%) and nasal whistling (20%). After surgery, there was an improvement in nasal obstruction in 70% of patients, nasal crusts in 87.5%, and epistaxis in 85.7% of patients. Corrections of external nasal valve dysfunction were achieved in 100% of patients. Columellar retraction and asymmetry of the nasal tip were observed in 80% and 90% of patients. In total, 62.5% and 55.5% of patients showed improvement after surgery, respectively. The increase of the nasal dorsum was performed with en block graft of costal cartilage, and diced cartilage wrapped in fascia. The resorption and diversion of cartilage grafts were minimal and did not result in significant changes in patient satisfaction. Conclusion: structural rhinoplasty with costal cartilage grafts permits a good quantity of cartilage in the manufacture of allowing a safe nasal reconstruction of the saddle nose due to leprosy. The use of diced cartilage wrapped with temporal fascia increased the nasal dorsum in patients with saddle nose by leprosy and showed a lower risk of twisting and allowed a more natural appearance to the nasal dorsum with satisfactory result. The septal L-strut reconstruction was essential in structuring the nose leading to good functional outcome, improvement of nasal patency, as well as decreased postoperative scar retraction at the post-operative time. According to the degree of satisfaction, patients reported improvement in quality of life and greater social acceptance due to good functional and aesthetic results with increased nasal patency.